Pseudomonas aeruginosa: host interactions and the identification of novel modulators of quorum sensing-mediated virulence - Bates, Robyn Hannah (2014)
Pseudomonas aeruginosa is a clinically important opportunist pathogen that is responsible for high levels of morbidity and mortality in the nosocomial environment. Due to the intrinsic antibiotic resistance of P. aeruginosa, coupled with a genomic flexibility that allows the acquisition of additional resistance mechanisms, treatment options against infections caused by this pathogen are dwindling. Therefore, there is now a drive to develop novel anti-pseudomonal therapeutics. In order to do this, it is important to gain increased understanding of P. aeruginosa at the molecular level. To this end, three different aspects of P. aeruginosa virulence were studied in this thesis. Previously, interactions between respiratory pathogens such as N. meningitidis and both the host platelet-activating factor (PAFr) and the 37/67 kDa laminin receptor have been demonstrated. P. aeruginosa also interacts with the host PAFr, therefore this study investigated whether it also binds the 37/67 kDa laminin receptor via the candidate surface proteins PilQ, the type IV pilus secretin, and OprI, a lipoprotein. Through ELISA and whole-cell pulldown experiments, this work has shown that although P. aeruginosa interacts with the 37 kDa laminin receptor precursor, the interaction is mediated only in part by PilQ and OprI and may occur at levels too low to be of physiological significance. The galactophilic lectin LecA is important in P. aeruginosa adhesion to host cells as well as cytotoxicity and biofilm maturation. The expression of the lecA gene is subject to complex growth phase-dependent regulation involving RhlR, RpoS and MvaT, and PqsE is also required. However, few direct regulators of the lecA promoter have been described. In promoter pulldown experiments, 22 candidate proteins including MifR, FleQ, MvaT, AlgP, RhlR and GbuR were identified bound to the lecA promoter region. For 18 of these candidate regulatory proteins, mutation resulted in altered LecA production. The effect of most of these mutations could be partially masked by homeostatic levels of PqsE, confirming its importance in the expression of lecA; however, mutation of AlgP and GbuR abolished the expression of LecA even in the presence of homeostatic levels of PqsE. LecA expression could be rescued in PAO1-W algP and gbuR mutants by the overexpression of the pqsE gene under the control of an IPTG-inducible promoter. Furthermore, FleQ, the major flagellar regulator, bound the lecA promoter region and also negatively regulated the production of LecA. Considering that lecA expression is indirectly regulated by AlgU and AmpR, the work presented here is consistent with a hypothetical regulatory pathway in which AmpR, SadB, AlgU and AmrZ converge upon FleQ to regulate lecA transcription. PqsE also negatively regulates the activity of the pqsA promoter via an unknown mechanism. Promoter pulldown experiments revealed a strikingly complex protein profile at the pqsA promoter during peak pqsA expression in both the presence and absence of PqsE. A group of 16 candidate regulators of the pqsA promoter were chosen for further investigation, such as SadB, ParR, FleQ and FleR. Intriguingly, many proteins that bound the lecA promoter also bound the pqsA promoter, including AlgP. This suggests that AlgP regulates the activity of the pqsA promoter, and therefore pqsE expression, and would explain why abrogation of LecA production caused by algP mutation can be overcome by the overexpression of pqsE. The construction of a pqsA-lux bioreporter would enable the impact of the candidate proteins on the activity of the pqsA promoter to be determined. The work carried out thus underlines the complexity of the P. aeruginosa regulatory networks and contributes through the identification of a number of additional regulatory proteins.